Pengaruh Financial experience dan Financial attitude terhadap Financial management behaviour melalui Locus of control pada Pegawai PT. Bank Pembangunan Daerah Jambi Cabang Bangko - Marlina Putri Ayu; Arna Suryani; Sudirman Sudirman (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
This study aims to determine and describe the picture of financial experience, financial attitude, locus of control and financial management behavior in employees of PT. Bank Pembangunan Daerah Jambi Bangko Branch and to determine and analyze the influence of financial experience and financial attitude on financial management behavior through locus of control in employees of PT. Bank Pembangunan Daerah Jambi Bangko Branch. This type of research uses descriptive verification research. This study uses the PLS analysis method. Based on the results of the study, it shows that financial experience and locus of control have a positive and significant effect on financial management behavior, while financial attitude does not have a significant effect on financial management behavior. However, financial attitude is still able to influence financial management behavior through locus of control as a mediating variable. The results of this study indicate that financial experience and self-control ability have an important role in shaping the financial management behavior of employees at PT. Bank Pembangunan Daerah Jambi Bangko Branch.